Analisis Usaha Pencucian Sepatu Di Kabupaten Dan Kota Bandung - Firman Hasandi Febriansyah; Deri Apriadi (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to analyze the development strategy of shoe washing and Medium Enterprises (SMEs) in facing increasingly tight competition. Shoe washing SMEs, as one of the business sectors with great potential, often face serious challenges, such as limited capital, low use of technology, and inconsistent service quality. This study uses a qualitative approach with a case study method on several urban laundry SMEs, which are analyzed using the Swot theoretical framework and Porter's Five Forces model. The results of the study show that laundry SMEs have strengths in competitive prices, proximity to customers, and strategic locations. However, the main weakness found is the lack of utilization of technology and innovation in services, which hinders business competitiveness. Existing opportunities, such as increasing awareness of sustainability-based services and digitalization, provide space for business development. The threat of competition with laundry franchises and changes in customer preferences that are increasingly moving towards fast and efficient services, are serious challenges for SMEs. Based on the results of the analysis, the recommended development strategies include the use of digital technology for management and marketing, improving service quality, innovation in types of services, and product diversification to attract new customers.